Potensi Senyawa Bioaktif dari Makroalga Hijau: Eksplorasi dan Implementasinya dalam Aplikasi Industri (Studi pada Ulvan) - Aznur, Bima Syifa; Darlingga, Mutiara (MAIYAH, 2023)
The marine ecosystem harbors a wealth of natural resources that can be transformed into high-value products, with green algae, particularly ulvan, being the focus of research. Ulvan, a unique sulfated polysaccharide from green macroalgae, offers potential as a bioactive compound with various activities. Chemical structure analysis of ulvan reveals its potential applications in the industry. Ulvan extraction techniques are critical steps in achieving optimal yields, while separation and characterization of ulvan fractions through chromatography and spectroscopy allow for the identification of specific compounds. Experiments indicate that ulvan possesses strong antioxidant activity, supporting its role in functional food formulations and nutraceutical supplements. In the pharmaceutical industry, ulvan is used in the development of anti-tumor drugs and immunostimulants, with clinical trials showing positive effects on immune responses and inhibition of tumor cell growth. In the cosmetic field, formulations containing ulvan demonstrate anti-aging effects and skin hydration. The application of ulvan in biotechnology involves the production of biomaterials and biofuels. The conversion of ulvan into biofuel through microbial fermentation shows potential as a renewable energy source. Ulvan is also utilized in the production of biomaterials for medical applications, such as wound dressings. Exploring the potential anti-hyperglycemic properties of ulvan opens opportunities for diabetes therapy. Challenges related to ulvan production efficiency and in-depth characterization need to be addressed. A profound understanding of ulvan's potential as a sustainable natural resource is expected to stimulate innovation across various industrial sectors. This research provides a comprehensive overview of natural resources that can shape the future of sustainable and environmentally friendly products